Type of integral and reduction for a generalized Birkhoffian system - Wu, Hui-Bin (惠彬 吴); Mei, Feng-Xiang (凤翔 梅) (Chinese physics B, 2011)
This paper studies a type of integral and reduction of the generalized Birkhoffian system. An existent condition and the form of the integral are obtained. By using the integral, the dimension of the system can be reduced two degrees. An example is given to illustrate the application of the results.